Analysis Of Rock Fragmentation Using Wipfrag At Lafargeholcim Rawang Quarry, Selangor - Abdul Rahman, Najihatul Nabihah (Universiti Sains Malaysia, 2018)
The assessment of fragmentation of muckpile are the critical element of managing any blasting operation. Rock fragmentation is considered the most important thing in quarrying because of its direct effects on the efficiency and cost of drilling and blasting, and after loading, hauling, and finally crushing operations. Rock fragmentation depends on two groups of variables; 1) rock mass properties which cannot be controlled, and 2) blast design that can be controlled and optimized. Image analysis systems have become practical and useful tools for measuring the performance of explosive in breaking rock, determining the validity of blast models and examining the efficiency of crushers and grinding. In this research, WipFrag software is used in the assessment of rock fragmentation from blasting at LafargeHolcim Rawang quarry. The results are in a form of size distribution graphs and evaluation are made by relating to the geological structures, blast design, powder factor and the strength of the limestone rocks. The geological features on research area was observed and described. Photographs for images analysis is taken after the blasting this is for the image analysis. Meanwhile rock samples are collected for point load test, PLT to determine the rock strength of the blasted rock. In this analyses, the geological features gives an effect on the performance of the blast even though the appropriate blast design is used.